TO THE ISSUE OF MODERN WORKING CLASS OF DAGESTAN - Rasulov, M A (History, Archeology and Ethnography of the Caucasus, 2015)
The author of the article attempts to examine the problem of modern working class of the Republic of Dagestan, this problem has fallen off the radar of researchers and become irrelevant in the market economy conditions. The number of working class of the Dagestan Republic was estimated basing on the statistical figures of 2011, but its agricultural detachment was not taken into account as there was no possibility for singling out rural workers from all employees involved in agriculture and related industries of the republic. The article presents the occupational structure of the workers due to their categories of qualification, dynamics of individual groups of workers in urban and rural areas as compared to the data of 1989. Besides, the article deals with the problem of special contingent of the working class–scattered groups of foreign workers who have effective permission of the authorities and are involved in various sectors of economy of the country and Dagestan Republic.